Implikasi Erupsi Gunung Agung Terhadap Usaha Pariwisata Di Daya Tarik Wisata Bahari Tulamben, Kecamatan Kubu, Kabupaten Karangasem - Ida Ayu Karina Putri; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2019)
Tulamben Marine Tourist Attraction it has a variety of tourism business such as, tourist accommodations, diving and snorkeling occupations, porter professions also food and beverage services. Mount Agung status alert, on October 22nd, 2017 some residents within radius of 12 km are evacuated to several areas in Bali. The evacuated people are living in 28 villages in Karangasem regency, one of them is Tulamben Village. Mount Agung eruption has a direct impact on tourism bussiness. This study aims to analyze the implication of Mount Agung Eruption on Tourism Business at Tulamben Marine Attraction, Kubu Sub-District, Karangasem Regency. The research method used is qualitative study with descriptive analysis technique to examine the implications of Mount Agung eruption on tourism business. Source data from primary knowledges and secondary documents. Data are collected through observation methods, interviews, literature study, and research instruments in the form of interview guidelines. The informants are determinated by using purposive sampling technique to obtain accurate data about the type of tourism business and the implications of eruption of Mount Agung to the tourism business service in Tulamben Marine Tourist Attraction. Keywords: Marine Tourist Atrraction, Eruption, and Tourism Bussines